Utilization of borax and its impact on the income and the livelihood of miners and other stakeholders: A case of Uganda. - James Natweta Baguma; Victoria Mukasa; D K Sekimpi; Daniel Sekabojja; Victoria Nabankema; Kamese Geoffrey; Eva Magambo; John Ssempebwa; Margrethe Smidth (PLoS ONE)
Background Mineral wealth serves as a crucial driver of economic growth and infrastructure development in many countries, including Uganda. Artisanal and Small-Scale Gold Mining (ASGM) plays a significant role in enhancing incomes and livelihoods. However, ASGM remains largely informal in Uganda, not reflected in the country's Gross Domestic Product (GDP). Many methods of gold processing are available around the globe. The borax method has become one of the favorable methods for extracting gold due to its lower operating cost, higher recovery, human and environmental consideration. This study aimed to assessing the impact of borax utilization in gold processing on the income and livelihoods of miners and stakeholders in Buhweju, Busia and Kassanda districts in Uganda where the Free Your Mine project is being implemented. Methods A cross-sectional study using mixed methods was employed between October 2022 and January 2023 with data collected from 161 miners through semi-structured questionnaires, Key Informant Interviews (KIIs), Focus Group Discussions (FGDs), and observations. Analysis was conducted using Atlas ti version 7.0 and Stata Version 15.0. Results Findings indicate low adoption of borax and limited training coverage on the use of borax. While 80.1% of respondents saved money attained from gold mining activities, only 21.5% had investments. FGDs revealed that miners often resort to mercury use for quick income as using mercury takes little time compared to mercury-free methods, while KIIs emphasized the need for government intervention and need for policies to promote safer gold processing methods for sustainable livelihoods. Conclusion Study underscores need for awareness, policy to improve safety in Uganda's ASGM sector. In addition, there is need for funding to support scale up the Free Your Mine Project to other gold mining districts in Uganda.